Ultra-Low-Dose Radiotherapy for Palliation of Mycosis Fungoides - İpek Pınar Aral; Neşe Göçer Gürok; Aykut Oğuz Konuk; Özlem Üçer (Hindawi Limited, 2020)
Introduction. Mycosis fungoides (MF) is a form of primary cutaneous T-cell lymphomas, and radiotherapy (RT) has been used to treat localized/limited lesions of MF. In this case report, the results of low-dose RT applied for palliative purpose are shared. Case Report. A 70-year-old male patient was admitted to the outpatient clinic 7 months ago with a generalized itchy rash. The result of the biopsy was reported as mycosis fungoides. Systemic treatment was not performed due to comorbid diseases. The hemibody RT was applied. 2 Gy was given per fraction, with a total dose of 6 Gy. The significant clinical relief was observed with 6 Gy RT. The patient died due to multiorgan failure 2 months later, and no recurrence was observed. Conclusion. The palliation was achieved in the advanced MF patient with fractionated 6 Gy hemibody RT for the remaining 2 months of life.